Efeitos isolados e combinados de ultrassom e de compostos químicos em morangos (Fragaria x ananassa Duch.) - Rosário, Denes Kaic Alves do (2016)
Consumers have become increasingly interested in food with microbiological safety, long self-life, and with minimal changes in the nutritional and sensory quality after processing. Then researchers have tried more efficient sanitization methods for removal of pathogenic and spoilage microorganisms in foods especially those consumed fresh like strawberries. This study aimed to evaluate the isolated and combined effect of using different chemicals (acetic acid, sodium dodecyl benzene sulphonate (DBSS), peracetic acid) and ultrasound (40 kHz) for the sanitization of strawberries and their influence on microbiological, physico-chemical and sensorial parameters, after sanitization and during the storage time of up to 9 days at 8 ± 1 °C. Analyses of aerobic mesophilic, filamentous fungi and yeast, lactic acid bacteria, total coliforms, E. coli, titratable acidity, pH, total soluble solids, color, vitamin C, weight loss, texture profile (firmness, cohesiveness and adhesion), and inactivation / removal of S. enterica, intentionally adhered to strawberry, were performed. It also carried out sensory analysis of ultrasound treatments associated with peracetic acid and washed with water. Results were analyzed by ANOVA, regression analysis and Duncan test at the 5% level of probability. After application of the sanitizing treatments on strawberries, the aerobic mesophilic count was reduced from 0.2 to 1.8 log CFU.g -1 , filamentous fungi and yeast, between 0.2 and 2.0 log CFU.g -1 , lactic acid bacteria from 0.4 to 2.0 log CFU g-1 and S. enterica from 0.5 to 2.1 log CFU.g -1 . The ultrasound combined with peracetic acid and peracetic acid isolated stood out, obtaining the largest reductions. Acetic acid and DBSS have its effects enhanced by ultrasound, achieving reductions of up to 1.0 and 1.1 log CFU.g -1 for filamentous fungi and yeasts. There were no significant difference (p < 0.05) for physico-chemical parameters between sanitization treatments, except for weight loss, in which treatments with DBSS led to more loss. There was no significant sensory difference (p < 0.05) among the treatments. This study demonstrated the high efficiency of peracetic acid when combined with ultrasound in sanitizing of strawberries and that ultrasound did not cause changes in physicochemical and sensory parameters evaluated.